Transcriptional signatures of unfolded protein response implicate the limitation of animal models in pathophysiological studies - Ze Zheng; Guohui Wang; Li Li; Jeffery Tseng; Fei Sun; Xuequn Chen; Lin Chang; Henry Heng; Kezhong Zhang (Wolters Kluwer Medknow Publications, 2016)
Background: The unfolded protein response (UPR) refers to intracellular stress signaling pathways that protect cells from the stress caused by accumulation of unfolded or misfolded proteins in the endoplasmic reticulum (ER). The UPR signaling is crucially involved in the initiation and progression of a variety of human diseases by modulating transcriptional and translational programs of the stressed cells. In this study, we analyzed the gene expression signatures of primary stress sensors and major mediators of UPR pathways in a variety of tissues/organs of human and murine species. Methods: We first analyzed protein sequence similarities of major UPR transducers and mediators of human and murine species, and then examined their gene expression profiles in 26 human and mouse common tissues based on the microarray datasets of public domains. The differential expression patterns of the UPR genes in human diseases were delineated. The involvements of the UPR genes in mouse pathology were also analyzed with mouse gene knockout models. Results: The results indicated that expression patterns and pathophysiologic involvements of the major UPR stress sensors and mediators significantly differ in 26 common tissues/organs of human and murine species. Gene expression profiles suggest that the IRE1α/XBP1-mediated UPR pathway is induced in secretory and metabolic tissues or organs. While deletion of the UPR trans-activator XBP1 leads to pathological phenotypes in mice, alteration in XBP1 is less associated with human disease conditions. Conclusions: Expression signatures of the major UPR genes differ among tissues or organs and among human and mouse species. The differential induction of the UPR pathways reflects the pathophysiologic differences of tissues or organs. The difference in UPR induction between human and mouse suggests the limitation of using animal models to study human pathophysiology or drugology associated with environmental stress.